Edukasi UMKM Abon Pindang Sebagai Bentuk Optimalisasi Potensi Desa di Desa Sudimara - Widyaningsih, Ni Putu Putri; Wijaya, I Gusti Agung Rendra; Ardani, Ni Nyoman; Sanjaya, Ananda Sherlly Viana; Hirun, Yohana Yoriwaty; Pramana, I Gede Nengah Dwi; Pendika, Komang Swananda; Parantika, I Ketut (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
MSMEs are an important part of economic development in Indonesia that can help alleviate poverty and improve the welfare of rural communities, including Sudimara Village. Sudimara Village has abundant marine potential because it is a coastal area. Many villagers process the marine products into pindang so this village is also known as a producer of pindang in Tabanan Regency. Fish processing is only done in pindang, and it is not processed into more innovative products that are more durable. Seeing the potential of pindang as a promising marine processed product, the Triatma Mulya University KKN team held an educational activity about the opportunities for abon pindang MSMEs in Sudimara Village. This activity aimed to motivate the community to package fishery potential into MSMEs products. The results obtained are that participants become aware of the village’s potential and new business opportunities. Through this activity, participants also got information that has never been taught regarding the right way to manage a business so that they are motivated to run UMKM abon pindang. In addition, the participants appeared enthusiastic and gave positive response to the abon pindang product that the Triatma Mulya University KKN team had made.